Comportamiento de conectores de cortante tipo canal en sistemas de entrepiso conformados por viguetas en celosía, concreto reforzado y lámina colaborante: Planteamiento de ecuación para cálculo de la capacidad de conectores (2019)
This article studies the mechanical behavior of channel-type shear connectors in mezzanine systems made up of lattice joists, reinforced concrete and collaborative sheet. For which, 25 specimens were manufactured and experimentally analyzed in the weak connector position within the valley of the collaborating sheet, which were subjected to direct shear testing. Based on the results obtained and the results obtained in the different investigations carried out to date by researchers Huertas [8], Hoyos [7] and Marulanda [9]. The results of 116 specimens were processed and an equation was proposed as an envelope that allows to reliably predict the capacity of channel-type shear connectors in these mezzanine systems.